Wujud Satuan Lingual Caption Dalam Surat Kabar Kompas Edisi Januari - Februari 2016 Dan Implementasinya Dalam Pembelajaran Bahasa Indonesia Di SMA Kelas X - Sari, Dewi Purnama; , Drs. Agus Budi Wahyudi, M.Hum (2016)
Caption is a label that is placed above or below the figures and tables. Caption is used as figures' information to replace, strengthen, and confirm a news. The purpose of this study is to explain language form of caption and referential meaning in the Kompas January-February 2016, also to implement the caption in the Kompas January-February as a teaching material in learning Indonesian in the high school twograde. Data source of this study is caption in Kompas January-February 2016. In the data collection, researcher used watch and noted techniques. The theory used is Alwi theory about capture being. Type of this study is qualitative descriptive. Researcher analyzed using intralingual match technique. This study shows that the provisions in the caption consists of figure's text should be made at least two sentences, the first sentence explains the figure, the second sentence and so on explain the data owned, figure's text should contain at least 5W + H, these are who, what, where, when, why + how, figure's text is created with simple present tense, and figure's text begins with information place of published figure, then broadcast date and title, also ended with the year of published figure and name of creator and editor. Caption shown on the figure is not a whole in accordance with the provisions of 5W + H caption, these are who, what, where, when, why + how, figure's text is created with simple present tense. Most of the caption in Kompas January-February 2016 does not use 5W + H. Keywords: Caption, referential meaning, Kompas.